Shear ultrasonic investigations of polyhydric alcohols - M. WACIŃSKI; R. PŁOWIEC (Archives of Acoustics, 2014)
The influence of the hydrogen bonds and the steric factor on the steady now viscosity (η0) and the limited shear elasticity (G∞) of polyhydric alcohols have been investigated by ultrasonic methods.